The relationship between durability and simulated cycling performance - Evans, G.; Muniz-Pumares, D. (Journal of Science and Cycling, 2025)
Introduction Durability, or the resilience to a downward shift in physiological markers of endurance performance following prolonged exercise, has been proposed as an important additional component of endurance performance. Durability could be particularly important in cycling races where performance is often determined by the ability to produce high power outputs after large quantities of accumulated work. However, the extent to which durability explains variation in performance is not yet fully understood, and there are a wide range of protocols to measure durability, which could lead to inconsistent findings. Therefore, the aims of this study were to a) determine whether the type of fatiguing protocol (continuous or intermittent) influences the effectiveness of durability to predict cycling performance and b) determine whether considering the durability of the markers of endurance performance helps predict cycling time trial (TT) and road race (RR) performance.